Youth unemployment in Canada, Germany, Ireland, and the United Kingdom in times of COVID-19 - Zechuan Deng; Rubab Arim; Golo Henseke; Ingrid Schoon; Hans Dietrich; Aisling Murray; Emer Smyth; Véronique Dupéré (Economic and Social Reports)
From the start of the COVID-19 pandemic, there were widespread concerns about young people’s labour market prospects. This article describes the COVID-19 youth economic activity and health monitor (YEAH) project at University College London (UCL) in collaboration with Statistics Canada and other institutes in Europe, which is aimed to shed light on this area by examining the pandemic’s impacts on the dynamics of youth employment and well-being.